3D scanner technology in the reverse engineering of complex mechanical components: A literature review - Afferli Seftian; Delima Yanti Sari; Rifelino Rifelino; Zainal Abadi (Researcher and Lecturer Society, 2026)
This study addresses the challenges involved in the reverse engineering of complex mechanical components, where conventional manual measurement methods often produce geometric deviations that negatively affect the reliability of advanced engineering analyses. A descriptive literature review was conducted to evaluate the role of 3D scanning technology in overcoming these limitations. The study compares various data acquisition methods, including laser scanning, structured light scanning, and photogrammetry, while also analysing how the level of geometric accuracy influences finite element simulation results and structural analysis outcomes. The review found that 3D scanning significantly improves geometric fidelity compared with traditional techniques, thereby enhancing the validity of numerical simulations. However, the review also identified that the quality of the final model is highly dependent on the selected scanning technology, surface conditions, and advanced reconstruction processes such as point cloud registration and mesh generation. The findings indicate that although 3D scanning offers superior precision, geometric deviations may still occur and influence structural parameters. This study concludes that the integration of 3D scanning into reverse engineering workflows requires systematic validation to ensure not only visual accuracy but also functional reliability in engineering applications. Furthermore, this review highlights a critical research gap, suggesting that future studies should place greater emphasis on the direct correlation between geometric accuracy and engineering simulation outcomes.